PENINGKATAN MOTIVASI KERJA MELALUI GAYA KEPEMIMPINAN - Rizaldi, Arjuna (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2017)
This research aims to find out the impact of leadership style to employees? motivation. The hypothesis proposed is that the employee?s motivation will improve if the leadership style used is able to fulfill the employee?s expectation. This research is conducted in the railway transport service company of the State-Owned Entities (BUMN) in Bandung. The respondents are the employees of the company. The questionnaires are distributed after doing validity and reliability tests. After that, the questionnaires are analyzed using Rank Spearman Correlation. The descriptive analysis shows that both leadership style and work motivation have a significant correlation.